Powder for magnetic cores, its manufacturing method and powder magnetic cores
Patent Information
- Application Number
- JP2021046370
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-19
- Publication Date
- 2025-03-12
- Estimated Expiration
- 2041-03-19
Smart Images

Figure 0007644336000002 
Figure 0007644336000003 
Figure 0007644336000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a powder for use in producing a dust core. [Background technology]
[0002] Electromagnetic devices such as electric motors, generators, various actuators, and transformers use an alternating magnetic field via a magnetic core (soft magnet). To improve the efficiency of electromagnetic devices, a magnetic core with excellent magnetic properties and low high-frequency loss (hereinafter simply referred to as "iron loss" regardless of the material of the magnetic core) is required.
[0003] Iron loss includes eddy current loss, hysteresis loss, and residual loss, of which eddy current loss increases in proportion to the square of the frequency of the alternating magnetic field. To reduce this eddy current loss, magnetic cores made of laminated electromagnetic steel sheets with insulating coating on the surface have been mainly used up until now.
[0004] However, recently, dust cores (compressed powder bodies of insulatingly coated soft magnetic particles) have been attracting attention because of their high degree of freedom in shape and their ability to reduce hysteresis loss, which increases in proportion to the frequency of an alternating magnetic field, in addition to eddy current loss. The following patent documents contain descriptions related to such dust cores: [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2004-288983 A [Patent Document 2] JP 2006-24869 A [Patent Document 3] JP 2013-142182 A [Patent Document 4] JP 2016-213306 A Summary of the Invention [Problem to be solved by the invention]
[0006] The powder magnetic cores described in the above patent documents are intended for use in inductors and reactors used in switching power supplies, DC / DC converters and the like, and are intended to be used in a frequency range of about 10 k to 100 kHz.
[0007] However, when the applications of powder magnetic cores are expanded to include electromagnetic devices used in lower frequency ranges (for example, 1.2 to 3 kHz), it becomes necessary to further reduce iron loss (for example, hysteresis loss), which is a problem in the low frequency range.
[0008] The present invention has been made in view of the above circumstances, and has an object to provide a method for producing powder for magnetic cores that can reduce iron loss (e.g., hysteresis loss) in powder magnetic cores. [Means for solving the problem]
[0009] As a result of intensive research conducted by the present inventors to solve this problem, they have newly discovered that it is possible to further reduce the iron loss (e.g., hysteresis loss) of a powder magnetic core by using soft magnetic powder obtained by further heating at high temperatures, crushing, and annealing a raw material powder made of an iron alloy. By expanding on this finding, they have completed the present invention, which will be described below.
[0010] <<Method of manufacturing magnetic core powder>> (1) The present invention provides a method for producing powder for magnetic cores, comprising: a calcination step of heating a first powder made of an iron alloy containing Si at 975 to 1175°C to obtain a calcined body; a crushing step of crushing the calcined body to obtain a second powder; and a powder annealing step of annealing the second powder to obtain a third powder.
[0011] (2) According to the manufacturing method of the present invention, a third powder (soft magnetic powder) consisting of powder particles with large crystal grain size and small residual strain and residual stress can be obtained. By using this third powder, it is possible to manufacture a dust core that can at least reduce hysteresis loss.
[0012] 《Magnetic core powder》 The present invention can also be understood as such a powder for magnetic cores. For example, the present invention may be a powder for magnetic cores made of soft magnetic particles that are made of an iron alloy containing Si and that satisfy the following: average particle size: 50 to 250 μm, average crystal grain size: 30 to 100 μm, and average particle hardness: 100 to 190 Hv. The powder for magnetic cores may be made of soft magnetic particles that are insulated to reduce eddy current loss in the powder core (to improve the resistivity of the powder core).
[0013] 《Powder magnetic core etc.》 The present invention can also be understood as a powder magnetic core obtained by compacting the above-mentioned magnetic core powder and a manufacturing method thereof. The manufacturing method of the powder magnetic core may include, for example, a compacting step of the magnetic core powder and a heat treatment (annealing) step of removing residual strain and residual stress introduced into the powder particles in the compacting step.
[0014] "others" Unless otherwise specified, "x to y" in this specification includes a lower limit of x and an upper limit of y. Any numerical value included in the various numerical values or numerical ranges described in this specification may be used as a new lower limit or upper limit to create a new range such as "a to b."
[0015] Unless otherwise specified, "x to y μm" in this specification means x μm to y μm. 2 The same applies to (etc.). [Brief description of the drawings]
[0016] [Figure 1] 4 is a photograph showing the state of the raw material powder after calcination. [Diagram 2] 1 is a micrograph of each crushed powder particle after calcination. [Diagram 3] FIG. 4 is a scatter diagram showing the relationship between the average crystal grain size of each powder particle after calcination and the calcination temperature. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present invention will be described in more detail by giving embodiments of the invention. One or more configurations arbitrarily selected from the present specification may be added to the configuration of the present invention described above. The contents described in this specification may also be applied to the powder for magnetic core, the powder magnetic core, and the manufacturing method thereof according to the present invention. The configuration related to the manufacturing method may also be the configuration related to the product. Which embodiment is best depends on the target, the required performance, etc.
[0018] Powder and manufacturing method (1) First powder The first powder is made of an iron alloy (soft magnetic material) containing Si. The Si content is preferably 1 to 4%, or more preferably 2 to 3.5%, of the entire iron alloy as 100% by mass (simply referred to as "%). If the Si content is too low, eddy current loss and hysteresis loss may increase. If the Si content is too high, hardness may increase and formability may decrease. In this specification, unless otherwise specified, the alloy composition is shown as a mass percentage relative to the entire iron alloy.
[0019] The iron alloy may contain Fe and inevitable impurities as the remainder other than Si, or may contain one or more modifier elements (e.g., Mn, Cr, Mo, Ti, Ni, etc.) other than Si that can improve the magnetic properties, resistivity, moldability, etc. of the powder magnetic core. Usually, the amount of modifier elements is small, and for example, the total amount of modifier elements is 3% or less, or even 1% or less, of the entire iron alloy. Note that part of Fe may be replaced with other ferromagnetic elements (Co, Ni, etc.).
[0020] The raw powder used for the first powder may be either an atomized powder or a pulverized powder, regardless of the manufacturing method. The atomized powder may be any of water atomized powder, gas atomized powder, and gas-water atomized powder. If an atomized powder made of pseudo-spherical particles is used, the aggressiveness between the particles is reduced, and the decrease in the resistivity value of the powder magnetic core due to insulation breakdown or the like (the increase in eddy current loss) can be suppressed.
[0021] The particle size of the powder particles is appropriately selected, but for example, the average particle size is 50 to 250 μm, or even 75 to 150 μm. If the particle size is too large, the eddy current loss of the powder core increases, and if the particle size is too small, the hysteresis loss of the powder core may increase.
[0022] Unless otherwise specified, the "average particle size" in this specification refers to the median size (D50: particle size at which the cumulative frequency is 50%) measured using a particle size distribution measuring device (e.g., a laser diffraction dry particle size distribution measuring device manufactured by HELOS & RODOS).
[0023] The first powder may be classified using a sieve of a predetermined mesh size (JIS Z8801:1982) (JIS Z2510:2004). This allows the iron loss of the powder core to be stably reduced. For example, raw material powder classified into 45 to 250 μm, 75 to 212 μm, or even 100 to 160 μm may be used as the first powder.
[0024] (2)Second powder The second powder is obtained, for example, through a calcination process in which the first powder is heat-treated, and a crushing process in which the calcined body obtained in the calcination process is crushed (including pulverization). In the calcination process, the first powder may be heated at a temperature and for a time period that causes crystal growth in the powder particles. The heating temperature in the calcination process (referred to as the calcination temperature) is, for example, 975 to 1175°C, 1000 to 1125°C, or even 1025 to 1075°C. The heating time is, for example, 0.4 to 3 hours, or even 0.7 to 2 hours.
[0025] The calcination temperature is high enough that a typical green compact (high-pressure compact of powder) can become a sintered body. However, unexpectedly, the first powder or its low-pressure compact (preform, etc.) did not become a sintered body even when heated at high temperatures, but remained as a solidified body (calcined body) that could be crushed or pulverized. The second powder obtained by crushing (and further pulverizing) the calcined body had approximately the same particle shape and average particle size as the first powder.
[0026] The calcination step and the crushing step can be performed under various atmospheres. When oxidation of the (surface) of the powder particles is to be suppressed, the calcination step and the crushing step are preferably performed in an inert atmosphere (an inert gas atmosphere such as a rare gas or nitrogen gas, a hydrogen reduction atmosphere, a vacuum atmosphere, etc.). When oxidation of the surface of the powder particles is permitted or the surface of the powder particles is intentionally oxidized, the calcination step and the like may be performed in a desired oxidizing atmosphere.
[0027] The crushing step is a step of returning the calcined body to a powder state, and is carried out for a predetermined time using a crusher, a pulverizer, or the like. For example, the process is carried out for about 0.5 to 5 hours, or 1 to 3 hours, using a ball mill. The crushing step is preferably carried out under conditions that can suppress the introduction of strain into the powder particles.
[0028] (3) Third powder The third powder is obtained through a powder annealing step in which the second powder is heated. In the powder annealing step, the second powder is heated at a temperature and for a time period that removes distortion, stress, and the like introduced into the powder particles in the calcination step and the crushing step. The heating temperature (referred to as the powder annealing temperature) is, for example, 550 to 850°C, 650 to 800°C, or 725 to 775°C. The heating time is, for example, 0.4 to 3 hours, or 0.7 to 2 hours. The heating atmosphere may be an inert atmosphere, as in the calcination step, or an intentionally oxidizing atmosphere, or the like.
[0029] (4) Insulation coating The magnetic core powder is preferably made of insulating coated powder particles (soft magnetic particles). By using such a magnetic core powder, a dust core with high resistivity and low eddy current loss can be obtained. Examples of the insulating layer formed on the surface of the soft magnetic particles include a resin layer, a glass layer, and an oxide layer. The resin layer is formed, for example, using a silicon resin (or silicone resin) that has excellent heat resistance. The glass layer is formed, for example, using a low melting point glass or a silicon resin. The oxide layer is formed, for example, by heating iron alloy particles containing Si, and is made of silicon oxide (SiO 2 etc.) and iron oxide (FeO, Fe 2 O 3 , Fe 3 O 4 The silicon resin, low melting point glass, etc. on the particle surface of the magnetic core powder not only serves as an insulating layer when the compact is heated (annealed, etc.), but can also serve as a binder that bonds the particles together. The dust core obtained in this way can have not only high resistivity, but also high strength.
[0030] 《Magnetic core powder》 The magnetic core powder is made of soft magnetic particles of an iron alloy containing Si. The soft magnetic particles, for example, have an average particle size of 50 to 250 μm or 75 to 150 μm (substantially the same as the first powder particles described above), an average crystal grain size of 30 to 100 μm or 45 to 75 μm, and an average particle hardness of 100 to 190 Hv or 150 to 185 Hv. The insulating coating of the soft magnetic particles may be formed during the molding stage of the magnetic core powder (the manufacturing stage of the powder magnetic core), or may be formed in advance before that.
[0031] The average crystal grain size in this specification is determined as follows. First, particles classified into 106 μm to 150 μm from the powder are embedded in resin, polished, and etched to prepare a specimen for observation. The specimen is observed under a microscope, and the cross-sectional area and number of crystals within the grain are determined for each particle in the obtained image. For all observed particles, the total cross-sectional area (S) is divided by the total number of crystals within the grain (N), and the diameter of the circle corresponding to the average crystal grain cross-sectional area is determined: d=2×{(S / N) / π} 0.5 The diameter (d) thus obtained is taken as the average crystal grain size.
[0032] The particles to be calculated may be all particles within a given visual field (0.6 mm×0.5 mm), or may be particles appropriately extracted from multiple visual fields (for example, about 50 to 100 particles).
[0033] The average particle hardness in this specification was determined as follows. Using the above-mentioned observation sample, the hardness of one point per particle was measured for 10 particles using a micro Vickers hardness tester (test load: 100 g). The arithmetic mean value of the Vickers hardness thus obtained was taken as the average particle hardness.
[0034] The average particle hardness reflects the degree of strain and stress remaining in the soft magnetic particles. In other words, it is believed that the smaller the average particle hardness, the less strain and stress remaining in the particles (in other words, the smaller the coercive force). Therefore, it is believed that the use of a magnetic core powder with a smaller average particle hardness leads to a powder core with a smaller hysteresis loss.
[0035] <Production method of powder magnetic core> The powder magnetic core can be obtained, for example, by a manufacturing method including a filling step of filling a die having a cavity of a desired shape with the above-mentioned magnetic core powder, a molding step of compressing the powder to form a compact, and an annealing step of annealing the compact. The molding step and the annealing step are performed, for example, as follows.
[0036] (1) The compacting process can be carried out under various compacting pressures, but the higher the compacting pressure, the higher the density and magnetic flux density of the powder magnetic core that can be obtained. One high-pressure compacting method is the die lubrication warm high-pressure compaction method. The die lubrication warm high-pressure compaction method includes a filling process in which the magnetic core powder is filled into a die whose inner surface is coated with a high-fatty acid-based lubricant, and a warm compacting process in which the powder is compacted at a temperature and pressure that produces a metal soap coating separate from the high-fatty acid-based lubricant between the powder and the inner surface of the die.
[0037] Here, "warm" refers to, for example, a molding temperature (mold temperature) of 70° C. to 200° C., or even 100 to 180° C. The die lubrication warm high-pressure molding method is described in detail in, for example, Japanese Patent Publication No. 3309970 and Japanese Patent Publication No. 4024705.
[0038] (2) The annealing step is carried out for the purpose of removing the distortion and stress remaining in the particles due to the compacting step. This reduces the coercive force and hysteresis loss of the powder core. The annealing temperature is appropriately selected depending on the composition of the powder particles, and is, for example, 500 to 900°C or 650 to 800°C. The heating time is, for example, 0.1 to 5 hours or 0.5 to 2 hours. This annealing step is usually carried out in an inert atmosphere.
[0039] 《Powder magnetic core》 (1) The higher the density of a powder magnetic core, the higher the magnetic properties it can have. For this reason, the relative density is preferably, for example, 95% or more, 96% or more, or even 96.3% or more. The relative density is calculated by dividing the true density (ρ 0 ) to bulk density (ρ) ratio (ρ / ρ 0 ).
[0040] (2) Powder magnetic cores are used in a variety of applications and can take various forms depending on the application. Powder magnetic cores are used, for example, as magnetic cores for electric motors (including generators), actuators, transformers, induction heaters (IH), etc.
[0041] Incidentally, motors for electric vehicles (EVs) are being rotated at higher speeds than before, and attempts are being made to further reduce the size relative to the output. EV motors are used to drive vehicles, so they are required to have low iron loss even in low rotation ranges (low frequency ranges) where eddy current loss is not dominant. The powder magnetic core of the present invention is suitable for the iron core of the field element side or armature side (particularly the stator side) of such high-speed electric motors. For example, the powder magnetic core of the present invention reduces iron loss (particularly hysteresis loss) even in a frequency range of 3 kHz or less. In the case of a motor with 8 magnetic poles, for example, frequencies of 1.2 kHz, 2.0 kHz, and 3 kHz correspond to (maximum) rotation speeds of 18,000 rpm, 30,000 rpm, and 45,000 rpm, respectively. EXAMPLES
[0042] Powder magnetic cores were produced using various magnetic core powders obtained under different processing conditions, and the properties of the powder magnetic cores were evaluated. The present invention will be described in more detail based on these specific examples.
[0043] 《Magnetic core powder》 (1) First powder (raw material powder) Gas-atomized powder made of Si-containing iron alloy (Fe-3%Si) was prepared as the raw material powder. In the present examples, the alloy composition is expressed in terms of mass percentage (mass%) unless otherwise specified.
[0044] The raw powder was classified using a sieve (mesh size: #50), and the powder with a particle size of less than 300 μm was used as the first powder. The average particle size of the first powder was measured using the particle size distribution measuring device described above and found to be 94.3 μm (D50). Sample 2 shown in Table 1 was prepared by classifying the raw powder into particle sizes of 45 μm or more and less than 250 μm using two different sized sieves (#330, #60). The average particle size was measured in the same manner and found to be 100.2 μm (D50).
[0045] (2) Second powder (calcination process) Each first powder (200 g) was placed in an alumina crucible and heated in a furnace at each calcination temperature shown in Table 1. At this time, the inside of the furnace was made into a vacuum atmosphere and then preheated (1×10 -2 The first powder was heated at a rate of 12°C / min to the target calcination temperature in an inert atmosphere (Ar gas flow: about 90 kPa x 400°C x 1 hour) and heated at each calcination temperature for 1 hour. After this heating, the first powder was furnace-cooled (cooled in the furnace with an inert atmosphere).
[0046] The state of the first powder heated at each calcination temperature is shown in Figure 1. As is clear from Figure 1, only when the first powder was heated at 1050°C (975°C or higher) (samples 1, 2, and C1 in Table 1), a calcined body in which the first powder was solidified was obtained (calcination process).
[0047] The first powder heated at 900°C (sample C2 in Table 1) was put into a mortar and crushed lightly to prepare the second powder. The first powder heated at 750°C (sample C3 in Table 1) was used as the second powder as it was.
[0048] The calcined body obtained by heating the first powder at 1050°C was placed in a ceramic pot of φ100mm×100mm with φ10mm alumina balls (approximately 1 / 3 of the ceramic pot volume) and 100g of the first powder, and was crushed in a ball mill (100 rpm×1 hour) to obtain the second powder (crushing step). Note that it was confirmed by sieving that the particle size of each of the second powders was approximately the same as that of the first powder (less than 300 μm or less than 250 μm).
[0049] (3) The third powder (powder annealing process) The crushed second powders of Samples 1 and 2 were heated in a furnace at 750° C. The heating conditions were the same as those in the above-mentioned calcination step, except for the heating temperature. In this way, third powders of Samples 1 and 2 were obtained.
[0050] (4) Insulation coating (warm mixing process) The soft magnetic powder (samples 1 and 2 were the third powder, and samples C1 to C3 were the second powder) was mixed with a resin powder ("KR220L" manufactured by Shin-Etsu Chemical Co., Ltd.) (mixing step). The amount of the resin powder was 0.5 parts by mass relative to the soft magnetic powder (100 parts by mass). The mixed powder was placed in a container and heated to soften the resin powder, which was then kneaded with a glass rod (130°C x 15 minutes). After that, the kneaded product was cooled to room temperature while moving the glass rod. In this way, a magnetic core powder was obtained, which was made of coated particles in which soft magnetic powder particles were coated with silicone resin. The insulating coating process was carried out under atmospheric pressure.
[0051] 《Powder magnetic core》 Using each of the magnetic core powders described above, powder magnetic cores were produced as follows.
[0052] (1) A carbide mold having a ring-shaped cavity was prepared. The inner peripheral surface of the mold was TiN-coated to a surface roughness of 0.4Z. The mold was preheated with a band heater to set the inner wall temperature of the cavity to 130°C.
[0053] A 1% aqueous solution of lithium stearate was sprayed onto the inner surface of the cavity of the heated mold using a spray gun. 3 The solution was uniformly applied at a rate of about 100 / min. The aqueous solution was prepared by adding a surfactant and an antifoaming agent to water. The surfactants used were polyoxyethylene nonylphenyl ether (EO)6, (EO)10, and borate ester Emulbon T-80. Each of these was added at 1% by volume to the entire aqueous solution (100% by volume).
[0054] The defoaming agent used was FS Antifoam 80. This was added at 0.2% by volume to the entire aqueous solution (100% by volume). The lithium stearate used had a melting point of about 225°C and a particle size of 20 μm. The amount of dispersion was 100 cm of the aqueous solution. 3 The amount was 25 g per sample. This was further pulverized using a ball mill (Teflon (registered trademark) coated steel balls: 100 hours) to obtain a stock solution. This stock solution was diluted 20 times to a final concentration of 1% and used for the above coating.
[0055] (2) Each magnetic core powder was filled into the cavity after the lithium stearate was applied (filling process).
[0056] The filled magnetic core powder was pressure-molded at 1600 MPa while the temperature inside the cavity was kept at a warm state of 130° C. In this way, a ring-shaped (outer diameter: φ39 mm × inner diameter φ30 mm × thickness 5 mm) green compact was obtained.
[0057] (3) Each green compact was heated in a furnace (750°C x 45 minutes) in a nitrogen atmosphere (13.3 kPa) (annealing step), thus obtaining a ring-shaped green compact (sample material).
[0058] Observation and Measurement (1) Average grain size The particles extracted from each of the second powders with different calcination temperatures were embedded in resin and etched with nital to prepare specimens for observation. The cross sections were observed with a scanning electron microscope (SEM). The observation images for specimens 1, C2, and C3 are shown in Figure 2.
[0059] The observed images of each sample were processed and the average crystal grain size was determined by the method described above. The results are also shown in Table 1. The relationship between the calcination temperature and the average crystal grain size is shown in Figure 3.
[0060] (2) Average particle hardness The average particle hardness of each soft magnetic powder (samples 1 and 2 were the third powder, and samples C1 to C3 were the second powder) before insulation coating was determined by the method described above. The results are also shown in Table 1.
[0061] (3) Iron loss A copper wire of φ0.5 mm was wound around the powder magnetic core (ring-shaped) of each sample, and the iron loss (hysteresis loss and eddy current loss) was measured when an AC magnetic field of 1 T and 2 kHz was applied using an AC BH analyzer (manufacturer: Iwatsu Measurement Co., Ltd., model number: SY-8258). The results thus obtained are also shown in Table 1.
[0062] (4) Density The bulk density (ρ) of each sample powder core was calculated from the measured dimensions and weight. The true density (ρ0) of the powder core was also calculated based on the blending ratio of the resin powder and raw material powder used in the insulating coating and their true densities. The relative density (ρ / ρ0) of each powder core calculated from these is also shown in Table 1.
[0063] "evaluation" (1) Average grain size As is clear from Table 1 and FIG. 3, the powder particles of Samples 1, 2 and C1, which were calcined at a temperature of 1050° C., exhibited a significant increase in average crystal grain size.
[0064] (2) Iron loss Furthermore, as is clear from Table 1, the powder cores (samples 1 and 2) made of the third powder that was calcined at high temperature and then crushed and powder annealed showed a significant reduction in core loss (particularly hysteresis loss in the low frequency range (e.g., 2 kHz)). It was also found that the powder particles of samples 1 and 2 had a lower average particle hardness than the other powder particles.
[0065] (3) Discussion The reason why the iron loss of the powder cores of Samples 1 and 2 is small is believed to be as follows. In the powder particles of Samples 1 and 2, the crystals within the particles grew during the calcination process, and the residual strain and stress introduced by crushing the calcined body in the powder annealing process were also removed. Such powder particles also have a small coercive force, so it is believed that the hysteresis loss of the powder cores made of these powder particles was also greatly reduced. From the above, it was confirmed that the use of the magnetic core powder according to the present invention makes it possible to reduce the core loss (particularly the hysteresis loss in the low frequency range) of the powder magnetic core.
[0066]
Table 1
Claims
1. A calcination step of heating the first powder made of an iron alloy containing Si at 975 to 1175°C to obtain a calcined body; a crushing step of crushing the calcined body to obtain a second powder; a powder annealing step of annealing the second powder to obtain a third powder; A method for producing powder for magnetic cores comprising the steps of:
2. 2. The method for producing a powder for a magnetic core according to claim 1, wherein the powder annealing step heats the second powder at 550 to 850°C.
3. Made of an iron alloy containing Si, A magnetic core powder comprising soft magnetic particles that satisfy the following requirements: average particle size: 50 to 250 μm, average crystal grain size: 30 to 100 μm, and average particle hardness: 100 to 190 Hv.
4. The magnetic core powder according to claim 3, wherein the iron alloy contains 1 to 4 mass % of Si based on the total mass of the iron alloy.
5. 5. The powder for magnetic cores according to claim 3, wherein the soft magnetic particles are insulated.
6. A powder magnetic core obtained by compacting the powder for magnetic core according to any one of claims 3 to 5.
7. The powder magnetic core according to claim 6, which is used in an alternating magnetic field having a frequency of 1 to 3 kHz.
Citation Information
Patent Citations
JP1973063648A
Feeder for fastener band
JP1984019144A
Hydraulic turbine system for recovering power from cooling water
JP1985073066A
Dust core and method for manufacturing same
JP2004288983A
Dust core and manufacturing method thereof
JP2006024869A